Widening the Scope of National Testing Agency (NTA) - Singh, Jagdish; Bhardwaj, B.P. (JOURNAL OF INDIAN EDUCATION, 2021)
“The National Testing Agency (NTA) will work to offer a high-quality common aptitude test, as well as specialised common subject exams in the sciences, humanities, languages, arts, and vocational subjects, at least twice every year. It will serve as a premier, expert, autonomous testing organisation to conduct entrance examinations for undergraduate and graduate admissions and fellowships in higher educational institutions” (National Education policy, 2020 (P.54)). The assessment and evaluation is done for different purposes including shortlisting the candidate for admissions. It is essential to shortlist the best students from the bulk of applicants for the purpose of admission of the most deserving students in Higher Educational Institutions (HEIs). NTA, an autonomous body, has been created by the Government of India for the purpose of conducting examinations or tests for admission and for professional certification. At present, the responsibility of the agency is to conduct centralised testing for admission to various courses offered by the HEIs. International experiences demonstrate that centralisation of examinations help nations in improving the overall performance of education. This paper attempts to analyse different international experiences and suggest pathways to enhance the scope of NTA and also make it a statutory body that will provide teeth to it in terms of providing it financial and administrative autonomy.